2022
DOI: 10.1371/journal.pcbi.1010269
|View full text |Cite
|
Sign up to set email alerts
|

Inferring the nature of linguistic computations in the brain

Abstract: Sentences contain structure that determines their meaning beyond that of individual words. An influential study by Ding and colleagues (2016) used frequency tagging of phrases and sentences to show that the human brain is sensitive to structure by finding peaks of neural power at the rate at which structures were presented. Since then, there has been a rich debate on how to best explain this pattern of results with profound impact on the language sciences. Models that use hierarchical structure building, as we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 49 publications
(81 reference statements)
0
16
0
Order By: Relevance
“…A growing number of studies demonstrated how to measure the sensitivity of the brain to naturalistic speech for word-level features. It remains difficult to control for confounding aspects, such as in Ding, Melloni, et al (2016), where it has been argued that the chunking observed around syntactic phrases might be elicited simply by word-level occurrence statistics or by the repetition of part-of-speech tags (Frank and Yang, 2018;Ten Oever, Kaushik, and Andrea E Martin, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A growing number of studies demonstrated how to measure the sensitivity of the brain to naturalistic speech for word-level features. It remains difficult to control for confounding aspects, such as in Ding, Melloni, et al (2016), where it has been argued that the chunking observed around syntactic phrases might be elicited simply by word-level occurrence statistics or by the repetition of part-of-speech tags (Frank and Yang, 2018;Ten Oever, Kaushik, and Andrea E Martin, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Meyer, Sun, and Andrea E Martin, 2020b;L. Meyer, Sun, and Andrea E Martin, 2020a;Ten Oever, Kaushik, and Andrea E Martin, 2022;Haegens and Golumbic, 2018;Obleser and Kayser, 2019b). The interpretation of the role, cause and effect, of low-frequency oscillations in particular is not clear.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence shows that during successful comprehension, low-frequency neural activity becomes aligned with linguistic units such as phonemes and syllables 1,2 . This “neural tracking” effect was initially shown for these lower-level linguistic units, but more recently it has been observed for higher-level and rather abstract units such as words and phrases as well [39]. While syllables can be physically characterized by salient energy increases 10 , these higher-level units have no one-to-one physical correlates in the speech signal, meaning that they require endogenous computations to support neural tracking 11,12 .…”
Section: Introductionmentioning
confidence: 93%
“…Instead, the head position effect calls for a mechanism that resolves temporal inconsistency by inferring linguistic structure from the signal (cf. 9 ). A candidate mechanism of such kind is the "time-based binding" mechanism described in a computational model of neural oscillations 54 .…”
Section: Tracking Structural Regularitiesmentioning
confidence: 99%
See 1 more Smart Citation